Focal Spot and Wavefront Sensing of an X-Ray Free Electron laser using Ronchi shearing interferometry. Issue 1 (December 2017) - Nagler, Bob; Aquila, Andrew; Boutet, Sébastien; Galtier, Eric; Hashim, Akel; S. Hunter, Mark; Liang, Mengning; Sakdinawat, Anne; Schroer, Christian; Schropp, Andreas; Seaberg, Matthew; Seiboth, Frank; et al.
Abstract The Linac Coherent Light Source (LCLS) is an X-ray source of unmatched brilliance, that is advancing many scientific fields at a rapid pace. The highest peak intensities that are routinely produced at LCLS take place at the Coherent X-ray Imaging (CXI) instrument, which can produce spotsize at the order of 100 nm, and such spotsizes and intensities are crucial for experiments ranging from coherent diffractive imaging, non-linear x-ray optics and high field physics, and single molecule imaging. Nevertheless, a full characterisation of this beam has up to now not been performed. In this paper we for the first time characterise this nanofocused beam in both phase and intensity using a Ronchi Shearing Interferometric technique. The method is fast, in -situ, uses a straightforward optimization algoritm, and is insensitive to spatial jitter.